Simo decoction curing spleen deficiency constipation was associated with brain-bacteria-gut axis by intestinal mucosal microbiota - Yi, Xin; Zhou, Kang; Deng, Na; Cai, Ying; Peng, Xinxin; Tan, Zhoujin (Frontiers in Microbiology, 2023)
Background: Simo decoction (SMD) is a traditional prescription for treating gastrointestinal diseases. More and more evidences prove that SMD can treat constipation by regulating intestinal microbiota and related oxidative stress indicators, but the specific mechanism is still unclear. Methods: A network pharmacological analysis was used to predict the medicinal substances and potential targets of SMD to alleviate constipation. Then 15 male mice were randomly divided into normal group (MN group), natural recovery group (MR group), and SMD treatment group (MT group). Constipation model mice were constructed by gavage of Folium sennae decoction and control of diet and drinking water, and SMD was used for intervention after successful modeling. The levels of 5-hydroxytryptamine (5-HT), vasoactive intestinal peptide (VIP), superoxide dismutase (SOD), malondialdehyde (MDA) and fecal microbial activities were measured, and the intestinal mucosal microbiota was sequenced. Result: Network pharmacology analysis showed that a total of 24 potential active components were obtained from SMD, and 226 target proteins were obtained after conversion. Meanwhile, we obtained 1,273 and 424 disease-related targets in the GeneGards database and the DisGeNET database, respectively. After combination and deduplication, the disease targets shared 101 targets with the potential active components of SMD. When the mice were intervened with SMD, the 5-HT, VIP, MDA, SOD content and microbial activity in MT group were close to MN group, and Chao 1 and ACE in MT group were significantly higher than that in MR group. In the Linear discriminant analysis Effect Size (LEfSe) analysis, the abundance of beneficial bacteria such as Bacteroides, Faecalibacterium, Alistipes, Subdoligranulum, Lactiplantibacillus, and Phascolarctobacterium in MT group increased. At the same time, there were some associations between microbiota and brain-gut peptides and oxidative stress indicators. Conclusion: SMD can promote intestinal health and relieve constipation through brain-bacteria-gut axis associating with intestinal mucosal microbiota and alleviate oxidative stress.